The Effectiveness of the Negative Modification Extinction Method in Correcting Bullying Behavior among Primary School Female Students - التميمي نجاة علي صالح (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The current research aims to identify the effectiveness of the Negative Modification Extinguishment Method in modifying bullying behavior among primary school students in schools affiliated with the General Directorate of Education in Diyala for morning classes for the academic year (2024-2025). The researcher intentionally selected (20) female students from the Cairo and Hind Al-Makhzoumiya schools as two experimental and control groups. The researcher adopted the Tamimi Bullying Scale (2022) and developed a guidance program based on the Negative Modification Extinguishment Method. After implementing the program, the researcher reached the following conclusions:There were no statistically significant differences between the average scores of the control group members in the pre-test and post-test on the bullying scale. There were statistically significant differences between the average scores of the experimental group members in the pre-test and post-test on the bullying scale after applying the Negative Modification Extinguishment Method. There were statistically significant differences at the significance level of (0.05) between the scores of the control and experimental groups in the post-test, in favor of the experimental group.The research reached a set of conclusions, including: Bullying behavior results from several factors, including (internal, familial, and acquired). The method of extinguishing negative modification can be used to solve educational problems, starting from the elementary stage and up to university students. The activities and events included in the therapeutic counseling method are highly effective in modifying bullying behavior. Female students in elementary schools are in dire need of psychological counseling methods based on the scientific study of their needs and problems. Therefore, this research aims to modify undesirable behaviors The researcher also made a number of recommendations and suggestions.